Upscaling communication skills training – lessons learned from international initiatives. Issue 2 (February 2021) - Ammentorp, Jette; Bigi, Sarah; Silverman, Jonathan; Sator, Marlene; Gillen, Peter; Ryan, Winifred; Rosenbaum, Marcy; Chiswell, Meg; Doherty, Eva; Martin, Peter
Highlights: Communication Training based on the Calgary-Cambridge guide proves successful across countries. Experienced trainers are a precondition for the success of the programs. It is vital to adapt the training programs to the local needs and circumstances. Resources need to be prioritized to guarantee the sustainability of the programs. The RE-AIM framework can give a useful overview of the implementation process. Abstract: Objective: To collect experiences and to identify the main facilitators and barriers for the implementation process of large scale communication training programs. Methods: Using a multiple case study design, data was collected from leaders of the individual programs in Australia, Ireland, Austria and Denmark. The RE-AIM framework was used to evaluate the components: Reach, Effectiveness, Adoption, Implementation, and Maintenance of the programs. Results: The programs, all based on the Calgary-Cambridge Guide, succeeded in reaching the intended target groups corresponding to between 446 and 3000 healthcare workers. New courses are planned and so far the outcome of the intervention has been investigated in two countries. The fact that implementation, including educating trainers, relies on a few individuals was identified as the main challenge. Conclusion: Large scale communication training programs based on the Calgary-Cambridge Guide can be implemented and adopted in multiple different healthcare settings across a national health system culture. The importance of standardized trainer education and adaption of the programs to clinical practice was highlighted. Practice Implications: In order to address the sustainability of the programs and to allow the intervention to scale up, it is important to prioritise and allocate resources at the political and organizational level.